Effectiveness of netboard-based learning management system (LMS) nutrition education on nutritional intake of pregnant women - Kadir, Sunarto; Suardi; Indrawati, Lia (Berita Kedokteran Masyarakat, 2025)
Purpose: Analyzing the effect of nutrition education through a Netboard-based Learning Management System (LMS) on the nutritional intake of pregnant women in the working area of the Kota Tengah Community Health Center, Gorontalo Province. Methods: This study employed a quasi‑experimental design with pre‑test and post‑test measures. This study was conducted with two groups: an experimental group that received nutrition education through a Netboard-based LMS, and a control group that received education through conventional methods. The sample consisted of 40 second‑trimester pregnant women in the catchment area of the Kota Tengah Community Health Center, assigned to the experimental group (n=20) and the control group (n=20). Data were collected using a 3 × 24‑hour food recall form that covered indicators of macronutrient and micronutrient intake, as well as dietary patterns. The data were analyzed using an Independent Samples t‑test. Results: The results showed that Netboard‑based LMS nutrition education had a significant effect on pregnant women's dietary intake. The analysis yielded a significance value of 0.000 (< 0.05), with the experimental group demonstrating higher mean scores than the control group. Conclusion: Netboard-based LMS nutrition education effectively enhances the nutritional intake of pregnant women. Notably, 95% of participants in the experimental group achieved a 'good' intake classification post-intervention, compared to only 5% in the control group. This suggests that the digital platform is a promising tool for nutrition education in maternal health settings.